(untitled) (Epidemiology, Biostatistics, and Public Health, 2022)
In this paper we present the R implementation of a GLIM macro which fits age-period-cohort model following Osmond and Gardner. In addition to the estimates of the corresponding model, owing to the programming capability of R as an object oriented language, methods for printing, plotting and summarizing the results are provided. Furthermore, the researcher has fully access to the output of the main function (apc) which returns all the models fitted within the function. It is so possible to critically evaluate the goodness of fit of the resulting model